2018
DOI: 10.1002/slct.201803001
|View full text |Cite
|
Sign up to set email alerts
|

Surface functionalization of magnetic nanoparticles via palladium‐catalyzed Diels‐Alder approach

Abstract: Metal nanoparticles are currently being used as substantial catalysts for a number of classical chemical transformations. In contrast, performing novel biochemical reactions with the help of nano‐organocatalysts is highly underdeveloped area in chemical synthesis. In order to prepare an efficient nano‐organocatalyst, facilitated stable covalent bonding would be achieved by using Diels‐Alder reactions on the surface of magnetic nanoparticles. Herein, we report the synthesis of magnetic nano‐organocatalysts by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 26 publications
0
53
0
Order By: Relevance
“…Effect of temperature on reaction was also investigated for this purpose parallel reactions were conducted at different temperatures under ultrasonication. It was observed that with increasing temperature (30,35,40,45, 50°C) the yield of the desired product increased, but best yield was obtained with 45°C in 96% yield in 1 h under ultrasonication (Figure 8).…”
Section: Catalytic Performancementioning
confidence: 98%
See 1 more Smart Citation
“…Effect of temperature on reaction was also investigated for this purpose parallel reactions were conducted at different temperatures under ultrasonication. It was observed that with increasing temperature (30,35,40,45, 50°C) the yield of the desired product increased, but best yield was obtained with 45°C in 96% yield in 1 h under ultrasonication (Figure 8).…”
Section: Catalytic Performancementioning
confidence: 98%
“…[28] Additionally, it brings important advantages such as eliminates the formation of byproducts (bistriazoles and diacetylenes), removal of the catalyst from the reaction media which can be achieved by simple filtration and, especially minimize the effective metal loading for reaction (recyclability and reusability). Recently, different heterogeneous supports [29][30][31][32][33][34][35][36] such as zeolites, montmorillonite, [37] chitosan, [38,39] graphene oxide, [31,40] cellulose [33,41] have been used for immobilization of copper, but these methods have some deficiencies such as long reaction time, use of organic solvents, high temperature, tedious work-up procedure, low yield, high catalyst loading so it is worthwhile to develop a new, convenient, widely applicable, green, sustainable, feasible and regio-controlled synthetic methodology for the facile preparation of fluorescent biologically important 1,2,3-triazoles.…”
Section: Introductionmentioning
confidence: 99%
“…So far too much various strategies have been employed in this regard [25][26][27][28][29]. One of the well-known strategies is [4+2] cycloaddition (CA) approach with one-pot mechanism [30]. Protection of the Fe 3 O 4 NPs against damaging to the core/shell structure, is the most important advantage of one-pot mechanisms such as CA and click chemistry rather than mechanism with successive reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, various conditions for carrying out the CA reaction onto the NPs surfaces are experimented by using ultrasound wave irradiation and the obtained results are compared with microwave radiation and reflux methods. In this work, vinyl-modified Fe 3 O 4 NPs have been prepared according to procedures introduced in literature and used as dienophile moiety of CA reaction [30]. For this purpose, thiophene (1), anthracene (2), 1,3-cyclohexadiene (3), 4-(1E,2E)-3-phenylallylidene aminophenol (4), and melamine (5) were used as diene moieties (scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of successful examples of silica‐coated MNPs in different synthesis areas such as carbon–carbon coupling, acetylation, oxidation, hydrogenation and asymmetric synthesis are reported.…”
Section: Introductionmentioning
confidence: 99%